## A = 3(B + C) a.b=(a.c)/3 b.b=(3a.c)/3 b.=(a.3c)/3 solve for b

Question

Lost your password? Please enter your email address. You will receive a link and will create a new password via email.

Lorem ipsum dolor sit amet, consectetur adipiscing elit.Morbi adipiscing gravdio, sit amet suscipit risus ultrices eu.Fusce viverra neque at purus laoreet consequa.Vivamus vulputate posuere nisl quis consequat.

## Answers ( No )

B = A over 3 so put the three under the a and -c . a =3 (B+C) divide both sides by 3. A over 3 a equals B plus c subtract C from both sides. B = A over 3 – C I hope this helps so B = (A/3) – C remember divide both sides by 3 subtract C from both sides